Thermomechanical industrial processes : modeling and numerical simulation - Bergheau, Jean-Michel (London : ISTE ; Hoboken, NJ : Wiley, 2014)
The numerical simulation of manufacturing processes and of their mechanical consequences is of growing interest in industry. However, such simulations need the modeling of couplings between several physical phenomena such as heat transfer, material transformations and solid or fluid mechanics, as well as to be adapted to numerical methodologies. This book gathers a state of the art on how to simulate industrial processes, what data are needed and what numerical simulation can bring. Assembling processes such as welding and friction stir welding, material removal processes, elaboration proce.
Chapter 4. Material Removal Processes by Cutting and Abrasion: Numerical Methodologies, Present Results and Insights4.1. Introduction; 4.2. Methodologies for the cutting process study; 4.2.1. Cutting analytic formulations; 4.2.2. Cutting numerical models; 4.2.3. Results and discussion; 4.3. Methodologies for the study of process affectations; 4.3.1. Modeling approach; 4.3.2. Abrasive process; 4.3.3. 3D turning; 4.4. Bibliography; Chapter 5. Finite Element Approach to the Sintering Process at the Grain Scale; 5.1. A description of the sintering process at the grain scale.
Includes bibliographical references and index.
Print version record.
Keywords: Manufacturing processes -- Mathematical models; Manufacturing processes -- Congresses; Materials science -- Congresses; Metals -- Congresses; Sheet-metal work -- Mathematical models -- Congresses; TECHNOLOGY & ENGINEERING -- Industrial Engineering; TECHNOLOGY & ENGINEERING -- Industrial Technology; TECHNOLOGY & ENGINEERING -- Manufacturing; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; Manufacturing processes -- Mathematical models; Electronic books